From Graphite to Graphene: The Confinement of the Fermi Surface to the Line KH. (7th May 2013) - Bross, Helmut
Abstract : The graphite structure is self-consistently calculated by use of the all electron Modified Augmented Plane Wave (MAPW) scheme with lattice constants c considerably enlarged above the experimental value of graphite. Overall, the band structures of the series are found to be quite similar: the energy levels of the highly symmetric states K and H almost coincide, essentially fixing the Fermi level of the semimetallic solid. The dispersion along lines parallel to the atomic planes, already small in graphite at the experimental value of c, continues to flatten with increasing value of c . The structure with an interlayer distance enlarged by the factor 3 over the experimental value provides a good approximation of the behaviour of a monoatomic sheet. In this context, the unusual behaviour of graphene appears in a new light.